Dissociation among hemodynamic measures in asymptomatic high grade carotid artery stenosis - Marshall, Randolph S (J Neurol Sci, 2016)
BACKGROUND: Cerebral blood flow (CBF) regulation is a critical element in cerebrovascular pathophysiology, particularly in large vessel disease, but the best method to use for hemodynamic assessment is not clear. We examined 4 different blood-flow related measures in patients with unilateral high-grade carotid artery disease, assessing asymmetry between the occluded vs non-occluded side, and the correlations among the measures. METHODS: Thirty-three patients (age 50-93, 19M) with unilateral 80-100% ICA occlusion but no stroke underwent: 1) mean flow velocity (MFV) in both middle cerebral arteries by transcranial Doppler (TCD), 2) quantitative resting CBF using pseudo-continuous arterial spin labeling (pCASL) MRI, 3) Vasomotor reactivity (VMR) in response to 5% CO2 inhalation, and 4) Dynamic cerebral autoregulation (DCA) assessing the counter-regulation of blood flow to spontaneous changes in blood pressure using TCD monitoring and finger photoplethysmography. Paired T-tests and Pearson correlations assessed side-to-side differences within each measure, and correlations between measures. RESULTS: CBF (p=.001), MFV (p<.001), VMR (p=.008), and DCA (p=.047) all showed significantly lower values on the occluded side. The 4 measures were independent of each other on correlation analysis, even when controlling for age and anterior circle of Willis collateral (all partial correlations <.233 and p-values >.468). CONCLUSIONS: These 4 measures showed high sensitivity to the occluded carotid artery, but their dissociation suggests that any given measure only partially characterizes the hemodynamic state. Additional research is needed to explore the multifaceted biology of cerebral blood flow regulation.